Right-sized equipment - Bollinger, Steven R.; Rembiesa, David; Goodin, Kate (Manufacturing insights)
This program shares real-world applications of lean manufacturing principles, including: (a) How the production flow of parts used in de-icing airplane wings improved by making the assembly in a small cell; (b) How the cost of some parts decreased by as much as 75% just by reducing floor space and changing to right size equipment; and (c) Analysis of the Japanese term "chaku-chaku" and what it means to utilize people rather than machines.